2013
DOI: 10.1136/bcr-2013-200466
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomelanosis duodeni in a postrenal transplant patient

Abstract: SUMMARYPseudomelanosis duodeni is a rare entity characterised by dark pigmented intracellular granules seen within macrophages that lie within the lamina propria of the duodenal villi. There is no known treatment, and the clinical significance and long-term sequelae of this entity are unclear. We present a case of pseudomelanosis duodeni in a 54-year-old woman who presented with a 1-month history of nausea, vomiting and non-bloody diarrhoea. The medical history was significant for diabetes mellitus type 2, end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…This demonstrates that the majority of the pigmentation in the setting of DP is due to iron deposition. The main use of Fontana-Masson stain in routine histochemistry is to demonstrate melanin deposition, but none of the Fontana-Massonpositive cases included in this review were interpreted as melanin [19,21]. A single case stained positive for both Perl's Prussian blue and Fontana-Masson [25].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that the majority of the pigmentation in the setting of DP is due to iron deposition. The main use of Fontana-Masson stain in routine histochemistry is to demonstrate melanin deposition, but none of the Fontana-Massonpositive cases included in this review were interpreted as melanin [19,21]. A single case stained positive for both Perl's Prussian blue and Fontana-Masson [25].…”
Section: Discussionmentioning
confidence: 99%
“…La patogenia no es clara, puede estar relacionada con el depósito de hierro secundario a hemorragia intramucosa o a alteración del transporte después del suplemento de hierro sulfato oral, difiere de la "melanosis" coli en la naturaleza del pigmento descrito por lipofuscina y no melanina, la melanina no contiene hierro y los melanocitos no están presentes en la mucosa gastrointestinal, la pigmentación marrón negruzca de la mucosa se debe a la administración de laxantes antraquinónicos derivados de plantas como la cáscara sagrada, el sen, la frángula, el aloe autoadministrados en casos de estreñimiento crónico 6,7 . Esta alteración se ha observado entre la sexta y séptima década de la vida, la mayoría son mujeres, con antecedentes de hipertensión arterial, insuficiencia cardíaca crónica, insuficiencia renal crónica, hemorragia gastrointestinal, usuarios de propanolol, hidralazina e hidroclorotiazida, la terapia con hierro oral tiene la más fuerte asociación [8][9][10] . Se considera una condición benigna y puede ser reversible, su patogénesis y significación clínica aún no se han definido, se ha propuesto que puede haber una correlación entre la pigmentación de la Pseudomelanosis Duodeni y la absorción deteriorada de nutrientes, lo que puede resultar clínicamente en dispepsia, esto explica que los pacientes presenten malestar e indigestión, otros son asintomáticos 11,12 .…”
Section: Discussionunclassified
“…A benign finding of gastric and duodenal melanosis are such infrequent and manifest conditions that can lead to an extensive, expensive, and ultimately unnecessary work-up. It involves the collection of dark pigmented granules inside the macrophages of the duodenal villi’s lamina propria, usually within the apical tips ( 2 ). Prussian blue and Fontana-Masson stains can be used to detect these pigments in macrophages located within the lamina propria ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, melanosis could be a consequence of mucosal iron deposition following intramucosal hemorrhage. Electron probe microanalysis though has revealed that these same macrophages also contain hemosiderin, lipofuscin, and lipomelanin ( 4 ).…”
Section: Discussionmentioning
confidence: 99%